Study of Teacher-Student Interaction in Building Social Cohesion with Autistic Children - Yustina Yustina; Muamar Asykur; Hardiyono Hardiyono (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to analyze the forms of teacher interactions with autistic students, their impact on social cohesion between regular and autistic students, as well as factors that support and hinder the formation of social cohesion in inclusive learning at SD Inpres Benteng Jampea No. 57, Selayar Islands. This study uses a qualitative approach with a case study research type. Research informants consist of class teachers and regular students who are directly involved in the inclusive learning process. Data collection techniques are carried out through interviews, observation, and documentation, while data analysis uses the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that teacher interactions with autistic students take place through adaptive verbal communication, individual approaches, involvement in learning activities and group work, and providing emotional reinforcement during the learning process. These interactions have an impact on the development of social acceptance of regular students, involvement of autistic students in group work, the growth of peer empathy, and the role of teachers as social mediators in the classroom. Social cohesion is supported by the active role of teachers, the open attitude of regular students, group learning, social interaction habits, and inclusive communication, but is still influenced by the communication limitations of autistic students, teacher competence, inclusive facilities, and heterogeneous classroom conditions. Thus, teacher pedagogical interaction plays a crucial role in strengthening students' social cohesion in inclusive learning.